2017
DOI: 10.1107/s2052520616017844
|View full text |Cite
|
Sign up to set email alerts
|

Charge density analysis of metformin chloride, a biguanide anti-hyperglycemic agent

Abstract: The experimental charge density analysis of the anti-hyperglycemic agent metformin chloride with high-resolution X-ray diffraction data at low temperature (100 K) has been performed and these experimental results were compared with that derived from the corresponding periodic theoretical calculations at the B3LYP/6-31G** level of theory. The experimental and theoretical multipolar charge-density analyses of metformin chloride have been accomplished in order to understand its structural and electronic propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
4
10
0
Order By: Relevance
“…It is found that at all temperatures the ESPs of all static and dynamic charge densities possess similar features on the 0.5 e Å À3 isosurfaces of the electron densities: the most negative values appear near O atoms and the most positive values appear near H atoms. These features are in agreement with the presence of intermolecular hydrogen bonds in the crystal, and they are in line with similar features observed for static ESPs of other molecules (Kalaiarasi et al, 2016;Niranjana Devi et al, 2017;Zhurova et al, 2016). Major differences between ESPs on these isosurfaces are found between MEM densities and model densities, with a 60% larger range of values ÁV S for the MEM densities.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…It is found that at all temperatures the ESPs of all static and dynamic charge densities possess similar features on the 0.5 e Å À3 isosurfaces of the electron densities: the most negative values appear near O atoms and the most positive values appear near H atoms. These features are in agreement with the presence of intermolecular hydrogen bonds in the crystal, and they are in line with similar features observed for static ESPs of other molecules (Kalaiarasi et al, 2016;Niranjana Devi et al, 2017;Zhurova et al, 2016). Major differences between ESPs on these isosurfaces are found between MEM densities and model densities, with a 60% larger range of values ÁV S for the MEM densities.…”
Section: Discussionsupporting
confidence: 77%
“…Quantitative measures of the ESP have been obtained as integral properties over this surface according to Politzer et al (2001) (see Table 1 Table 1 Definitions of integral quantities of the ESP, integrated over isosurfaces of the electron density according to Politzer et al (2001 Sum of positive and negative variances of the ESP Degree of the electrostatic balance derived from the variances of the ESP atoms act as acceptors of intermolecular hydrogen bonds, and these three H atoms are part of a hydrogen bond too (Mondal et al, 2012). These features of the molecular ESP are in agreement with similar features of ESPs of other molecules (Kalaiarasi et al, 2016;Niranjana Devi et al, 2017;Zhurova et al, 2016). The ESP of the static electron density of AH (20) has also been computed for a cluster of 3 Â 3 Â 3 unit cells.…”
Section: Computational Details 31 Details Of the Algorithmsupporting
confidence: 69%
See 1 more Smart Citation
“…This cation does not result only from the protonation of TBG on one of its N atoms, but also from the migration of one proton from one N atom to another. This structure has also been observed previously during the protonation of biguanidium chloride (Ş erb et al, 2014;Niranjana et al, 2017). The reaction mechanism of its formation is believed to proceed via a tautomeric equilibrium leading to the more stable tautomer form.…”
Section: X-ray Diffraction Studysupporting
confidence: 80%
“…One method of analysis comprises the consideration of the ESP on a surface enveloping the molecule. In applications to small and large molecules up to proteins, the ESP has thus been used to identify electrophilic and nucleophilic sides, to characterize hydrogen bonds, and to analyse intermolecular interactions ( Dauter, 2016;Niranjana Devi et al, 2017;Sirohiwal et al, 2017;Zarychta et al, 2015;Zhurova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%